KEBIJAKAN PENEGAKAN HUKUM PIDANA TERHADAP PENANGGULANGAN MONEY LAUNDERING DALAM RANGKA PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Sri Endah Wahyuningsih; Rismanto Rismanto (Jurnal Pembaharuan Hukum, 2015)
Criminal law enforcement policy on prevention of money laundering in the context of criminal law reform in Indonesia can be started with the establishment of an appropriate legal products through through the government and passed by the House of Representatives, the readiness of law enforcement, protection for whistleblowers, reverse proof, constraints faced in the implementation of policies enforcement of criminal law on prevention of money laundering in the context of criminal law reform in Indonesia, the Increasing Money Laundering, human resources investigator’s ability is limited, Lack of coordination among law enforcement agencies, Prevention and Eradication of Money Laundering in the form a the Reporting Center and Financial analysis hereinafter referred PPATK. This institution is an independent agency that has the authority and duty to examine the suspected actions related to money laundering.